The use of detrital zircon data in terrane analysis: A nonunique answer to provenance and tectonostratigraphic position in the Scandinavian Caledonides - Slagstad, T.; Kirkland, Chris (Geological Society of America, 2017)
The Scandinavian Caledonides are conventionally described as a stack of parautochthonous to allochthonous nappes with more exotic units residing at structurally higher levels, from Baltica derived at the base to Laurentia derived at the top. Detrital zircon geochronology has been increasingly used for determining provenance and, by implication, tectonostratigraphic position. We present detrital zircon U-Pb-Hf results from the structurally highest, inferred Laurentia-derived Uppermost Allochthon. The data from the Uppermost Allochthon are statistically indistinguishable from those of the Lower and Middle Allochthons, and from other Neoproterozoic and younger metasediments around the North Atlantic. Detrital zircon U-Pb ages and Lu-Hf compositions fail the test of paleogeographic uniqueness, which is a prerequisite for using this tool to distinguish Laurentian from Baltican provenance, and therefore it cannot be used to infer tectonostratigraphic position.